2013
DOI: 10.1074/mcp.m112.025346
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Protein Pathway Activation Mapping of Adipose-Derived Stem Cell Differentiation Implicates Novel Regulators of Adipocyte Differentiation

Abstract: Next to embryonic stem cell research, adult stem cell research is providing a promising alternative for enhanced tissue regeneration and transplantation. The key biochemical networks controlling the differentiation processes regulating stem cell biology remain largely disputed and or undefined, contributing to a lack of knowledge of the principle phosphoregulatory events propagating signal transduction. To effectively monitor these events relative to adipocyte differentiation, this study utilized a high throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…As mentioned above, c-Abl was found to be involved in differentiation of diverse cell types (15)(16)(17)(18), whereas a recent proteomic analysis showed that it may be a novel adipogenic regulator (21). As we demonstrated, c-Abl inhibition caused a dramatic adipogenic abrogation, underlying its role as a key regulator of this process.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…As mentioned above, c-Abl was found to be involved in differentiation of diverse cell types (15)(16)(17)(18), whereas a recent proteomic analysis showed that it may be a novel adipogenic regulator (21). As we demonstrated, c-Abl inhibition caused a dramatic adipogenic abrogation, underlying its role as a key regulator of this process.…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, c-Abl is highly expressed in human adipocytes (19) and activated upon insulin stimulation, where it participates in regulation of metabolic downstream signals (20). Furthermore, a recent proteomic analysis placed c-Abl as a potential key regulator of adipogenesis (21).…”
mentioning
confidence: 99%
“…There is evidence showing that c-Abl plays a central role in CML and neurodegenerative diseases [12,45]. Recently, extensive studies have linked c-Abl to islet beta cell survival and adipogenesis [20,21,23,24]. By utilising genetic ablation and pharmacological inhibition, we found a new role for c-Abl in regulating diet-induced obesity and insulin resistance in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…A proteomic analysis revealed that c-Abl was a potential key regulator of adipogenesis via regulation of the expression and activity of peroxisome proliferator-activator receptor γ 2 (PPARγ2), the master adipogenic regulator controlling adipogenesis [23,24]. These findings indicate that c-Abl participates in adipocytes metabolism regulation in vitro.…”
Section: Introductionmentioning
confidence: 96%
“…DNBs have great significance in disease classification and monitoring, therapeutic response evaluation, early diagnosis and understanding of molecular pathogenesis 5 . As a few examples, a Bayesian network model has been developed to classify subjects with Alzheimer’s disease using longitudinal magnetic resonance data 26 , Yang et al 27 proposed a dynamic network approach to identify a prognostic signature for acute myeloid leukemia, and a dynamic protein pathway activation of adipose-derived stem cell differentiation identified novel biomarkers of adipocyte differentiation 28 .…”
Section: Resultsmentioning
confidence: 99%